Financial Toxicity and Coping Strategies in Workers with Chronic Illnesses - Widjaja, Cynthia; Suwartono, Christiany (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2025)
Current study aims to examine the relationship between financial toxicity and coping strategies among workers living with chronic illnesses. Financial toxicity refers to the psychological and economic distress caused by the high and ongoing costs of medical treatment. A quantitative method with a correlational design was employed. A total of 124 participants who were workers with at least one type of chronic illness were recruited using convenience sampling. Data were analyzed using Spearman’s correlation to determine the strength and direction of relationships between variables. The results revealed no significant correlation between overall financial toxicity and coping strategies. However, the behavioral disengagement dimension showed a significant negative correlation with financial toxicity, whereas the planning dimension demonstrated a significant positive correlation. These findings suggest that individuals with chronic illnesses tend to exert less effort when facing financial strain; however, once they feel sufficiently confident, they begin to plan strategies to manage their condition. The study contributes to understanding the psychological dynamics between financial stress and coping mechanisms among workers with chronic diseases.